KONTRIBUSI KEKUATAN OTOT LENGAN DAN BAHU DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP HASIL SERVIS ATAS DALAM PERMAINAN BOLA VOLI SISWA PUTRA SMA NEGERI 5 PEKANBARU - Ayuningtyas, Retno Putri; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine how much the contribution of arm and shoulder muscle strength, the contribution of wrist flexion and flexion of arm and shoulder muscles and wrist flexion with volleyball service in male students of SMA Negeri 5 Pekanbaru. This research was conducted at a volleyball court at SMA Negeri 5 Pekanbaru Jalan. Bawal No.43, Wonorejo, Kec, Marpoyan Damai, Pekanbaru City, Conducted from January to Juli 2020 with the number of samples studied was 12 people. Based on the results of research and data processing using statistical procedures, it was concluded that there is a significant relationship between arm and shoulder muscle strength and wrist flexion on the results of service where: there is a contribution of arm and shoulder muscle strength to the results of upper service) where rtab is at the level significant (0.05) = 0.602 means r count (0.27)> rtab (0.602) and the contribution is 7.29%. There is a contribution of wrist flexibility to the results of services above) where rtab significant level (0.05) = 0.602 means r count (0.79)> rtab (0.602) and its contribution is 62.41% and there is contribution of arm and shoulder muscles wrist strength and flexion. submit the results of services above) where the significant level of rtab (0.05) = 0.602 means r count (0.80)> rtab (0.602) r count and 64% contribution.Key Words: Contribution of Arm and Shoulder Muscle Strength, And Wrist Strength Hand,Service Results